Pengembangan Media Pembelajaran Berbasis Android Pada Mata Pelajaran Administrasi Sistem Jaringan Di SMKN 7 Sijunjung - Anjelina, Fira; Mary, Thomson; Irsyadunas, Irsyadunas (Jurnal Informatika, 2023)
This â€œstudy aims to determine the validity level of valid android-based learning media and to determine the practicality level of practical android-based learning media.Â  This study uses the Research and Developmentâ€ â€œ(R&D) method with the development model used, namely the ADDIE development model. The research subjects amounted to 15 people. Data collection techniques using a questionnaire with a Likert scale.The results of this study show that the average value of the media expert validity test is 0.80 and the material validity test is 1.04 with the valid category. The teacher's response practicality test showed a value of 97.77% and for the student's response practicality test showed a value of 94.11% with a very practical category. Conclusions based on assessments and input from material experts and media experts as well as the results of trials in the field of Android-based learning media have been tested for feasibility and can be usedâ€ as.